Developing Game "C-Hunter" for Learning C++ - Zainol Abidin, Muhammad Firdaus; Ab. Aziz, Mohamad Firdaus (Applied Information Technology And Computer Science, 2022)
This project is based on developing a video game called C-Hunter for learning the basic function of C++. The purpose of this game is for learning basic functions in C++ while having fun and enjoyable. Rapid Application Development Model is used as the method to develop this game. The notes and code used in this game are all related to the C++ programming language and focus only on function since the objective of this game is learning basic functions in C++. After collecting some information from user feedback, this game is quite as expected it to be that is, C-Hunter is a fun and enjoyable learning platform to use. Overall, this game has served its purpose, making the learning process much more fun and enjoyable. It also gives an impact on students since by using this game they can study in a nicer learning platform.